Pengembangan Sistem Booking Tenda dan Dekorasi Online Menggunakan Metode Waterfall dengan Integrasi Pembayaran Digital - Amalia Nur Hanifah; Sutarman Sutarman (Bulletin of Computer Science Research, 2025)
The rental systems for tents and decoration services in many regions are generally still managed manually through notebooks or text messages, which often leads to various operational issues. Common problems include delayed booking confirmations, transaction recording errors, difficulties in checking schedule availability in real time, and inefficient customer service workflows. These conditions hinder business processes and reduce customer satisfaction, especially in the digital era that demands fast, accurate, and integrated services. Therefore, a system capable of automating the booking process and providing digital payment mechanisms is required to ensure faster, safer, and more efficient transactions. This study aims to design and develop a web- and mobile-based booking system for tent and decoration rentals with integrated digital payment features. The research was conducted as a case study at Karisma Arga Decoration, Ponjong, Gunungkidul, Yogyakarta, using observation, interviews, and literature study to understand user needs and existing business workflows. The application was developed using the Laravel framework for the backend and React Native for the mobile platform, supporting digital payment methfods such as QRIS and e-wallets. The implementation results indicate that the system improves booking efficiency by up to 60% and reduces recording errors by 80%. Additionally, the system provides customers with the convenience of placing orders anytime and enables administrators to manage orders centrally. These findings demonstrate that digitalization plays a significant role in improving the professionalism and effectiveness of tent and decoration rental services in the era of Industry 4.0.